Bacteriophages Infecting Propionibacterium acnes. (11th April 2013) - Brüggemann, Holger; Lood, Rolf
Abstract : Viruses specifically infecting bacteria, or bacteriophages, are the most common biological entity in the biosphere. As such, they greatly influence bacteria, both in terms of enhancing their virulence and in terms of killing them. Since the first identification of bacteriophages in the beginning of the 20th century, researchers have been fascinated by these microorganisms and their ability to eradicate bacteria. In this review, we will cover the history of the Propionibacterium acnes bacteriophage research and point out how bacteriophage research has been an important part of the research on P. acnes itself. We will further discuss recent findings from phage genome sequencing and the identification of phage sequence signatures in clustered regularly interspaced short palindromic repeats (CRISPRs). Finally, the potential to use P. acnes bacteriophages as a therapeutic strategy to combat P. acnes -associated diseases will be discussed.